Does A Logical Coherence Relationship Exist between Strategic Financial Decisions? - Abid, Fathi; Trabelsi, Lotfi (Journal of Asian Business Strategy, 2012)
This paper investigates the logical ties between investment, financing and dividends decisions, creating the coherence of these three strategic financial decisions of the firm. Basing on results of a questionnaire addressed to a number of financial managers of firms, a comparative survey between two investigations, one achieved at United States (by W.Pruitt and Y.Gitman on a sample of 114 firms) and the other done in Tunisia (carried on a sample of 45 firms situated in different industrial zones) allows to give an appreciation of the coherence between financial decisions. Our results permit to explain the coherent behavior of strategic financial decision-makers through the analysis of the impact of every financial decision on two others.